Stališča visokošolskih učiteljev do rabe strojnoprevajalskih orodij pri pisanju v nemščini kot tujem strokovnem jeziku - Plos, Alenka (Vestnik za tuje jezike, 2025)
In the modern world, machine translation tools, such as Google Translate and DeepL Translator, have become an important tool in everyday personal and professional com-munication in foreign languages, as well as in the process of learning foreign languages. Their ease of use and accessibility are influencing the ways in which foreign languages (for specific purposes) are learned and taught, and raising pedagogical and ethical ques-tions. Whereas machine translation was in the past mainly the subject of research in the field of translation studies, it is now more intensively linked to research on foreign language learning, especially English, and much less research can be found on language pairs that do not include English. The paper examines the university teachers’ perspec-tives on the use of machine translation in writing in German as a foreign language for specific purposes. It focuses on how teachers assess and incorporate machine translation tools into the teaching and process of developing writing skills. Based on a qualitative empirical study, the findings reveal predominantly positive attitudes toward the integra-tion of such tools as supportive resources in teaching and writing in a foreign language for specific purposes. Teachers acknowledge the role of these tools in developing termino-logical knowledge, enhancing the understanding of specialized vocabulary, and fostering autonomous learning, especially among foreign students. However, they emphasize the need for critical use of these tools and highlight the importance of maintaining the devel-opment of learners’ own writing skills. The use of machine translation is not perceived as academic dishonesty, but rather as part of natural technological progress, provided their use is transparent and aligned with academic integrity. The paper thus opens a discussion on the importance of developing pedagogical strategies for the effective integration of these tools in the higher education foreign languages teaching and underlines the need to establish good practices that guide non-expert users (non-translators) toward the neces-sary critical use of machine translation.
Keywords: foreign language for specific purposes; machine translation; pisanje; stališča učiteljev; strojnoprevajalska orodja; teachers’ beliefs; tuji strokovni jezik; university teach-ers; visokošolski učitelji; writing